Tuberculous Lymphadenitis with Dark Specks Cytomorphology: Focus on the Presence of Eosinophils and History of Atopy in Children - Humairah Medina Liza Lubis; Nurcahaya Sinaga; Emni Purwoningsih; Qatrunnada Medina Salim; Muhammad Fathurridha Arabia Salim (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background. Research on eosinophils in lymph node cytology in tuberculous lymphadenitis (TBLN) patients with dark specks cytomorphology and its association with a history of atopies are still very little. Although neutrophils have been reported as predominant phagocytic cells in TB patients, eosinophils are also abundant in blood and lung tissue, but their role and pathogenesis are still unclear. Objective. To analyze the relationship between TBLN and eosinophils, dark specks, and history of atopy in pediatric TBLN patients. Methods. This study is a cross-sectional study of 35 indicative cytology results of patients with TBLN stained with May Grunwald Giemsa. Data on atopy history were measured by filling out the standard questionnaire of The International Study of Asthma and Allergies in Childhood (ISAAC). Results. Based on the cytological examination, 22 samples (62.9%) were found with positive eosinophils, and 13 samples (37.1%) with negative eosinophils. A total of 23 samples (65.7%) had a history of atopy. The Fisher's Exact Test results showed that TBLN with dark specks cytomorphology tends to find eosinophils with a test value of p=0.001, indicating a relationship between the two cytomorphological features. The results also showed a relationship between TBLN with dark specks cytomorphology with a history of allergies (p=0.038), and there was a relationship between the presence of eosinophils and a history of allergies (p=0.001). Conclusion.  Tuberculous lymphadenitis with dark specks cytomorphology was significantly associated with eosinophils and a history of atopy.Abstrak: Latar Belakang. Penelitian eosinofil pada sitologi kelenjar getah bening pada pasien limfadenitis tuberkulosis (LNTB) dengan sitomorfologi bintik gelap dan kaitannya dengan riwayat atopi masih terbatas. Meskipun neutrofil telah dilaporkan sebagai sel fagosit dominan pada pasien TB, eosinofil juga banyak ditemukan pada darah dan jaringan paru tetapi peran dan patogenesisnya masih belum jelas. Tujuan. Menganalisis hubungan antara LNTB dengan eosinofil, bintik gelap dan riwayat atopi pada pasien limfadenitis TB anak. Metode. Studi dilakukan secara cross-sectional dengan sampel 35 hasil sitologi indikatif pasien LNTB yang diwarnai dengan May Grunwald Giemsa. Data riwayat atopi diukur dengan pengisian kuesioner standar The International Study of Asthma and Allergies in Childhood (ISAAC). Hasil. Berdasarkan pemeriksaan sitologi didapatkan 22 sampel (62,9%) dengan eosinofil positif dan 13 sampel (37,1%) dengan eosinofil negatif. Sebanyak 23 sampel (65,7%) memiliki riwayat atopi. Hasil uji Fisher’s Exact menunjukkan bahwa LNTB dengan sitomorfologi bintik gelap cenderung ditemukan eosinofil dengan nilai uji p=0,001, menunjukkan adanya hubungan antara kedua gambaran sitomorfologi. Hasil penelitian juga menunjukkan adanya hubungan sitomorfologi LNTB dengan sitomorfologi bintik gelap dengan riwayat alergi (p=0,038), dan ada hubungan antara adanya eosinofil dengan riwayat alergi (p=0,001). Simpulan. Limfadenitis tuberkulosis dengan sitomorfologi bintik gelap berhubungan secara signifikan dengan eosinofil dan riwayat atopi.